Autonomous Chemotactic Light‐Emitting Swimmers with Trajectories of Increasing Complexity. (21st April 2021) - Pavel, Ileana-Alexandra; Salinas, Gerardo; Perro, Adeline; Kuhn, Alexander
Abstract : Autonomous Swimmers The cover illustrates article number 2000217 by Alexander Kuhn and co‐workers, describing the precise motion control of an electronic chemotactic swimmer. The image, created by the artist Lucia Ghegu, shows a firefly solving a maze to reach an area with high humidity, in analogy to the reported light emitting swimmer following a trajectory along a chemical gradient.